Economic crisis and political economy volume 2 : essays in honour of Tadeusz Kowalik - Bellofiore, Riccardo; Karwowski, Ewa; Toporowski, Jan; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Rosa Luxemburg, Oskar Lange and Micha? Kalecki made important contributions to twentieth century political economy that guided the thinking of their student Tadeusz Kowalik. The chapters of this volume examine how the ideas of Luxemburg, Lange, Kalecki and Kowalik can illuminate our understanding of the crisis in twenty-first century capitalism.
Keywords: Capitalism -- History -- 21st century; Political economy; Economic history; Economic theory; Economic policy